Crazy diffy!

Calculus Level 5

d 2 x d y 2 = 1 3 1 + ( d x d y ) 2 \dfrac { { d }^{ 2 }x }{ { dy }^{ 2 } } =\dfrac { 1 }{ 3 } \sqrt { 1+{ \left( \dfrac { dx }{ dy } \right) }^{ 2 } }

Consider the differential equation above. You are given that if y = 0 y = 0 , then x = 3 x=3 and d x d y = 0 \dfrac{dx}{dy} = 0 when x = 0 x=0 .

Find the value of x x when y = 6 y = 6 .

If the value you've found is z z , submit the answer as z \lfloor z \rfloor .


The answer is 38.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Feb 11, 2016

Putting p = d x d y p = \frac{dx}{dy} , the equation becomes d p d y = 1 3 1 + p 2 , \frac{dp}{dy} \; =\; \tfrac13\sqrt{1 + p^2} \;, which has solution p = sinh ( 1 3 y + c ) . p \; =\; \sinh\big(\tfrac13y+c) \;. Thus d x d y = sinh ( 1 3 y + c ) , \frac{dx}{dy} \; = \; \sinh\big(\tfrac13y+c) \;, and so x = 3 cosh ( 1 3 y + c ) + d . x \; = \; 3\cosh\big(\tfrac13y+c\big) + d \;. Since y = 0 y = 0 when x = 3 x=3 we have 3 = 3 cosh c + d 3 = 3\cosh c + d , and hence x = 3 cosh ( 1 3 y + c ) + 3 3 cosh c . x \; = \; 3\cosh\big(\tfrac13y+c\big) + 3 - 3\cosh c \;. Since p = d x d y = 0 p = \frac{dx}{dy} = 0 when x = 0 x=0 , we see that y = 3 c y = -3c at this point, and so 0 = x = 3 cosh 0 + 3 3 cosh c = 6 3 cosh c 0 \; = \; x \; = \; 3\cosh 0 + 3 - 3\cosh c \; = \; 6 - 3\cosh c so that cosh c = 2 \cosh c = 2 , and hence x = 3 cosh ( 1 3 y + cosh 1 2 ) 3 . x \; = \; 3\cosh\big(\tfrac13y + \cosh^{-1}2\big) - 3 \;. When y = 6 y=6 we have x = 3 cosh ( 2 + cosh 1 2 ) 3 = 38.418893464 x = 3\cosh\big(2 + \cosh^{-1}2\big) - 3 \,=\, 38.418893464\, making the answer 38 \boxed{38} .

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...